Interactive Exploration, Analysis, and Visualization of Complex Phenome–Genome Datasets with ASPIREdb. Issue 8 (20th May 2016) - Tan, Powell Patrick Cheng; Rogic, Sanja; Zoubarev, Anton; McDonald, Cameron; Lui, Frances; Charathsandran, Gayathiri; Jacobson, Matthew; Belmadani, Manuel; Leong, Justin; Van Rossum, Thea; Portales‐Casamar, Elodie; Qiao, Ying; et al.
Abstract : We developed ASPIREdb, an open‐source, interactive, easy to use Web application, which allows researchers to search, organize, analyze, and visualize variants and phenotypes associated with a set of human subjects. Investigators can annotate variants using publicly available reference databases and build powerful queries to identify subjects or variants of interest. ASPIREdb implements several standard statistical methods for analysis and exploration of data. Projects can be shared, allowing researchers to work collaboratively to build queries and annotate the data. ABSTRACT: Identifying variants causal for complex genetic disorders is challenging. With the advent of whole‐exome and whole‐genome sequencing, computational tools are needed to explore and analyze the list of variants for further validation. Correlating genetic variants with subject phenotype is crucial for the interpretation of the disease‐causing mutations. Often such work is done by teams of researchers who need to share information and coordinate activities. To this end, we have developed a powerful, easy to use Web application, ASPIREdb, which allows researchers to search, organize, analyze, and visualize variants and phenotypes associated with a set of human subjects. Investigators can annotate variants using publicly available reference databases and build powerful queries to identify subjects or variants of interest. Functional information and phenotypic associations of these genes are made accessible as well. Burden analysis and additional reporting tools allow investigation of variant properties and phenotype characteristics. Projects can be shared, allowing researchers to work collaboratively to build queries and annotate the data. We demonstrate ASPIREdb's functionality using publicly available data sets, showing how the software can be used to accomplish goals that might otherwise require specialized bioinformatics expertise. ASPIREdb is available athttp://aspiredb.chibi.ubc.ca .